Sex Differences in Characteristics and Outcomes in Elderly Heart Failure Patients With Preserved Ejection Fraction: A Post-hoc Analysis From TOPCAT - Sun, Jiaxing; Tai, Shi; Guo, Yanan; Tang, Liang; Yang, Hui; Li, Xuping; Xing, Zhenhua; Fu, Liyao; Zhou, Shenghua (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Although the impact of sex on patient outcomes for heart failure (HF) with preserved ejection fraction (HFpEF) has been reported, it is still unclear whether this impact is applicable for elderly patients with HFpEF. This study was conducted as a secondary analysis from a large randomized controlled trial—The Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist Trial (TOPCAT)—to evaluate the impact of sex differences on the baseline characteristics and outcomes of HFpEF patients who were older than 70 years. Methods: Baseline characteristic of elderly patients were compared between men and women. Primary outcomes were cardiovascular (CV) mortality and HF-related hospitalization, whereas secondary outcomes were all-cause mortality and all-cause hospitalization. Cox regression models were used to determine the effect of sex differences on patient outcomes. Results: A total of 1619 patients were included in the study; 898 (55.5%) women and 721 (44.5%) men. Age was similar between women and men. Women had fewer comorbidities but worse cardiac function than men. The rate of primary outcomes was lower in women than in men (18.4% vs. 27.5%; p < 0.001), including rate of CV mortality (8.9% vs. 14.8%; p < 0.001) and HF-related hospitalization (13.4% vs. 18.2%; p = 0.008). All-cause mortality was also lower in women than in men (15.6% vs 25.4%; p < 0.001). After adjustment for baseline characteristics, Cox regression analysis showed that female sex was a protective factor for CV mortality (hazard ratio [HR]: 0.53; 95% confidence interval [CI]: 0.40–0.73), HF-related hospitalization (HR: 0.71; 95% CI: 0.55–0.93), and all-cause mortality (HR: 0.59; 95% CI: 0.47–0.75). Although spironolactone significantly reduced the rate of all-cause mortality in women even after adjusting for baseline characteristics (HR: 0.68; 95% CI: 0.48–0.96; p = 0.028), no significant multivariate association was noted between sex and treatment effects (p = 0.190). Conclusion: Among elderly patients with HFpEF, women had worse cardiac function but better survival and lower HF-related hospitalization rate than men.